Answer:1124
Step-by-step explanation:
You have the answer correct
Answer:
y - 4 = 3(x- (-1) ---> y-4 = 3(x+1)
Step-by-step explanation:
y - 4 = 3(x + 1)
y - 4 = 3x + 3
y = 3x + 7
then plug in (-1,4)
4 = 3(-1) + 7
4 = -3 + 7
4 = 4
Point slope form looks like:
y - y₁ = m(x - x₁)
Answer:
why would he do that
Step-by-step explanation:
thats a lot for cheese. i can get it a dollar a pound
Answer:
x =√[y²+(27)²] = √[ z² - 3² +(27)²]
Step-by-step explanation:
step 1) x=√[y²+(27)²]
step 2)
We find y
z²=y²+3² → y² = z² - 3²
step 3) x = √[ z² - 3² +(27)²]